Exploring the significance of medical humanities in shaping internship performance: insights from curriculum categories - Chao Ting Chen; Anna Y.Q. Huang; Po-Hsun Hou; Ji-Yang Lin; His-Han Chen; Shiau-Shian Huang; Stephen J. H. Yang (Medical Education Online)
Background Medical Humanities (MH) curricula integrate humanities disciplines into medical education to nurture essential qualities in future physicians. However, the impact of MH on clinical competencies during formative training phases remains underexplored. This study aimed to determine the influence of MH curricula on internship performance.Methods The academic records of 1364 medical students across 8 years of admission cohorts were analyzed. Performance in basic sciences, clinical skills, MH, and internship rotations were investigated, including the subgroup analysis of MH curricula. Ten-fold cross-validation machine learning models (support vector machines, logistic regression, random forest) were performed to predict the internship grades. In addition, multiple variables regression was done to know the independent impact of MH on internship grades.Results MH showed the important roles in predicting internship performance in the machine learning model, with substantially reduced predictive accuracy after excluding MH variables (e.g. Area Under the Curve (AUC) declining from 0.781 to 0.742 in logistic regression). Multiple variables regression revealed that MH, after controlling for the scores of other subjects, has the highest odds ratio (OR: 1.29, p < 0.0001) on internship grades. MH explained 29.49% of the variance in internship grades as the primary variable in stepwise regression. In the subgroup analysis of MH curricula, Medical Sociology and Cultural Studies, as well as Communication Skills and Interpersonal Relationships, stood out with AUC values of 0.710 and 0.705, respectively, under logistic regression.Conclusion MH had the strongest predictive association with clinical competence during formative internship training, beyond basic medical sciences. Integrating humanities merits greater prioritization in medical curricula to nurture skilled, compassionate physicians. Further research should investigate the longitudinal impacts of humanities engagement.